2020
DOI: 10.1139/cjas-2019-0022
|View full text |Cite
|
Sign up to set email alerts
|

The source of performance and excretion data affects the environmental impact of pig rearing estimated by life cycle assessment

Abstract: The objective of this study was to calculate the environmental impact of raising pigs fed diets with 192, 182, 172, or 162 g kg−1 crude protein (CP) from 15 to 30 kg live weight, using a life cycle assessment (LCA) based on either predicted or observed performance and excretion data. The predicted data were calculated for two animal profiles: one with feed intake and weight gain data being representative of the national Brazilian average (yp-AVG), and the other being representative of the specific experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…To keep improving the environmental performance of animal production, quantified impacts should be included in the decision-making process at the farm or on the company scale ( 93 ) and for policy making ( 94 ). In this context, specificity and accuracy of data used to model animal performance and emissions is key to have reliable quantification of the effects of a strategy ( 95 ), and further research is encouraged to fill the gaps identified. Interaction with types of manure management and other mitigating measures has to be studied (precision feeding, technological measures, manure treatment, anaerobic digestion for energy production, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…To keep improving the environmental performance of animal production, quantified impacts should be included in the decision-making process at the farm or on the company scale ( 93 ) and for policy making ( 94 ). In this context, specificity and accuracy of data used to model animal performance and emissions is key to have reliable quantification of the effects of a strategy ( 95 ), and further research is encouraged to fill the gaps identified. Interaction with types of manure management and other mitigating measures has to be studied (precision feeding, technological measures, manure treatment, anaerobic digestion for energy production, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…If an increase in nitrogen losses in the manure is related to a given ingredient choice, it is expected that this modification will lead to higher GHG emissions and probably other major consequences too (65). In this context, strategies that mitigate nutrient excretion, such as enzyme supplementation (75), synthetic amino acid partially replacing protein crops, or the use of low-protein diets (6,42,57), can potentially mitigate the environmental impacts of both pig and poultry production. The modification of the feed formulation method (89) and the adoption of precision feeding techniques (46,90) are also very important and innovative tools.…”
Section: Importance Of Feeding Scenariosmentioning
confidence: 99%